(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: The introduction of Bulk-Fill (BF) composite materials, among other new preparations, was one of the most recent innovations in operative dentistry. All bulk composites' colour stability is a source of concern. There has been a lot of research on the effects of different drinking solutions on the colour consistency of conventional resin-based composites, but little has been written about the colour changes of BF composite resins, which have been developed for the placement of somewhat thicker layers. Aim: Thus, the objective of this systematic review was to assess the colour consistency of various bulk-filled composites. Methods and Materials: A massive exploration of preexisting literature was done in order to locate all relevant research that addressed the sustainability of colour of BF composites under the effect of various. According to PRISMA standards, the current systematic evaluation was carried out. A thorough search for non-controversial existing literature on the websites like PubMed portal, MEDLINE portal, and Scopus portal was done in December 2022. There were no comparable articles in Cochrane online library. To make sure that all pertinent studies were found, search keywords were applied. Furthermore, all appropriate scientific papers from Jan 2010 to December 2022 on the effect of various beverages, polishing techniques, storage media, and oral fluids, bleaching protocols on the colour longevity of bulk-filled composite samples were included. Results: 18 studies were evaluated in this systematic review. 9 studies focused on the effect of different drinks and beverages like tea, coffee, wine, and acidic beverages over the changes in the colour of bulk-filled composites. There were 4 studies that evaluated the impact of different polishing mechanisms. There were 2 researches that described the influence of different bleaching techniques over the change in colour of bulk-filled composites. One study discussed the effect of reinforcement of glass fibers and polythene fibers in bulk-filled composites, the presence of different dentin substitutes and water solubility and water sorption impact over the change in colour. The number of specimens evaluated ranged from n=20 to n=800 across all the included studies. There was the use of two to ten composite materials across all the included studies. Conclusion: When there was an analysis of the effect of different beverages and drinks over the changes in colour then there were mixed results. Some studies found that colour changes in bulk-filled composites are lesser than in customary composites. While some studies revealed that alteration in colour is greater in bulk-filled composites when compared to customary composites. Some studies found no significant difference in colour change in conventional composite and bulk-filled composite. The polishing operations can have a serious influence on the staining impedance of bulk-fill composite resins.